3-Total Edge Product Cordial Labeling for Stellation of Square Grid Graph - Rizwan Ullah; Gul Rahmat; Muhammad Numan; Kraidi Anoh Yannick; Adnan Aslam (Journal of Mathematics)
Let G be a simple graph with vertex set VG and edge set EG. An edge labeling δ:EG⟶0,1,…,p−1, where p is an integer, 1≤p≤EG, induces a vertex labeling δ∗:VH⟶0,1,…,p−1 defined by δ∗v=δe1δe2⋅δenmodp, where e1,e2,…,en are edges incident to v. The labeling δ is said to be p-total edge product cordial (TEPC) labeling of G if eδi+vδ∗i−eδj+vδ∗j≤1 for every i,j, 0≤i≤j≤p−1, where eδi and vδ∗i are numbers of edges and vertices labeled with integer i, respectively. In this paper, we have proved that the stellation of square grid graph admits a 3-total edge product cordial labeling.